Partisipasi Masyarakat dalam Pelaksanaan Kebijakan Pembinaan Rumah Tahfiz di Nagari Parambahan Kabupaten Tanah Datar - Zena Zharifa; M. Fachri Adnan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to explain community participation in the implementation of the tahfiz house development policy in Nagari Parambahan and explain the factors that affect community participation in the implementation of the tahfiz house development policy in Nagari Parambahan. This study uses a qualitative descriptive approach. Data collection was carried out through observation, interviews, and documentation studies. The informants consisted of the local government as the coach of the tahfiz house, the guardian of the Parambahan nagari, the manager of the tahfiz house, and the community as participants who were selected using purposive sampling. The validity of the data in this study uses source triangulation techniques and method triangulation. Data analysis using interactive models. The results of the study show that community participation in the implementation of the tahfiz house development policy in Nagari Parambahan, is still relatively low. In the form of material participation, participation is given by allowing the use of private houses owned by the community for tahfiz activities, but the house is not able to accommodate all students in the tahfiz house. In the form of physical participation, the participation given by becoming a volunteer teacher at the tahfiz house but the number of teachers who teach is not balanced compared to the number of students. The participation given by becoming a donor of the tahfiz house who routinely contributes funds to pay the salaries of teachers at the tahfiz house even though the funds collected are often insufficient